Proteostasis Dysfunction in Aged Mammalian Cells. The Stressful Role of Inflammation - Ruano, Diego (Frontiers in Molecular Biosciences, 2021)
Aging is a biological and multifactorial process characterized by a progressive and irreversible deterioration of the physiological functions leading to a progressive increase in morbidity. In the next decades, the world population is expected to reach 10 billion, and globally, elderly people over 80 are projected to triple in 2050. Consequently, it is also expected an increase in the incidence of age-related pathologies such as cancer, diabetes, or neurodegenerative disorders. Disturbance of cellular protein homeostasis (proteostasis) is a hallmark of normal aging that increases cell vulnerability and might be involved in the etiology of several age-related diseases. This review will focus on the molecular alterations occurring during normal aging in the most relevant protein quality control systems such as molecular chaperones, the UPS, and the ALS. Also, alterations in their functional cooperation will be analyzed. Finally, the role of inflammation, as a synergistic negative factor of the protein quality control systems during normal aging, will also be addressed. A better comprehension of the age-dependent modifications affecting the cellular proteostasis, as well as the knowledge of the mechanisms underlying these alterations, might be very helpful to identify relevant risk factors that could be responsible for or contribute to cell deterioration, a fundamental question still pending in biomedicine.